If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y(-2) = -6.8(-2) + 5 Reorder the terms for easier multiplication: -2y = -6.8(-2) + 5 Multiply -6.8 * -2 -2y = 13.6 + 5 Combine like terms: 13.6 + 5 = 18.6 -2y = 18.6 Solving -2y = 18.6 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '-2'. y = -9.3 Simplifying y = -9.3
| 3x+4(2x-12)=73 | | 5y+18y-(-2y)+(-10y)= | | 0.12=0.5y | | 0.12=0.5 | | 5m-7=12 | | 4p-8p=16 | | 3(2y-0.3)=19.4-9 | | 8x+9y=-10 | | 4y-17=90 | | 2x+x^2-59=0 | | 7y+8=90 | | -5b+21=8b-3(b-7) | | 5x+5(2x-12)=30 | | z-8x=5z-7-6z | | q^3-2q^2+1=0 | | 6x^3-17x^2+5x+6=0 | | -2/11x=4/15 | | (6y+5)+(8y-13)=90 | | P=9t^4ln(8t) | | 3(4.52)-2y=16.50 | | (8m-6)= | | 4x^2+28x=400 | | x+8x=24 | | sinx=0.2 | | 3/5y=3 | | x^2+7x=100 | | 3(4.52)-2y=x | | 3/4y=3 | | x^2+7x=400 | | 0.5x+10-0.2x=4 | | 11z+(3z-7)=119 | | 33+15w=3w-w+w |